Optimalisasi Pemeliharaan Drainase Berdasarkan Persepsi Masyarakat - Dian Febrianti; Cut Suciatina Silvia (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2019)
Drainage is one element of the general infrastructure needed by the community in order to lead a clean, comfortable, and healthy area of life. In this drainage, one of the things related to the problem of drainage, among others, is the occurrence of physical damage to the drainage, namely the damage that occurs in the drainage build-ing. One of the areas experiencing drainage problems is BlangBeurandang Village, BB1 Housing, Johan Pahla-wan District, West Aceh Regency. In this village, if there is rainfall with high intensity floods often occur. This is caused by the poor performance of the existing drainage such as a lot of sedimentation, siltation in channels that are still earth channels, as well as a lot of garbage and grass. Because of these problems, the role of the communi-ty in the maintenance of drainage is very important, because with the community participation in drainage mainte-nance this will certainly be able to minimize the occurrence of various problems related to drainage. The research method used is the Likert scale method. The result of this research is the existing condition of BB1 Housing drain-age, that is, if there is rainfall with high intensity, frequent flooding occurs. This is due to the poor performance of the existing drainage, such as a lot of sedimentation, siltation of channels that are still earth channels, as well as a lot of garbage and grass. Optimization of drainage maintenance based on community perceptions is classified as good criteria, this is shown from the calculated questionnaire percentage value of 72.09%. Based on the results of the calculation of the percentage, the community is very supportive for the maintenance of drainage in BB Housing.